Embodiment and Human Development - Marshall, Peter J. (Child Dev Perspect, 2016)
We are recognizing increasingly that the study of cognitive, social, and emotional processes must account for their embodiment in living, acting beings. The related field of embodied cognition (EC) has coalesced around dissatisfaction with the lack of attention to the body in cognitive science. For developmental scientists, the emphasis in the literature on adult EC on the role of the body in cognition may not seem particularly novel, given that bodily action was central to Piaget’s theory of cognitive development. However, as the influence of the Piagetian account waned, developmental notions of embodiment were shelved in favor of mechanical computational approaches. In this article, I argue that by reconsidering embodiment, we can address a key issue with computational accounts: how meaning is constructed by the developing person. I also suggest that the process-relational approach to developmental systems can provide a system of concepts for framing a fully embodied, integrative developmental science.